2017
DOI: 10.3389/fnins.2017.00174
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Gene Therapy: Surgical Vector Delivery in the Translation to Clinical Trials

Abstract: An exceptionally high number of monogenic disorders lead to incurable blindness, making them targets for the development of gene-therapy. In order to successfully apply therapeutic vector systems in vivo, the heterogeneity of the disease phenotype needs to be considered. This necessitates tailored approaches such as subretinal or intravitreal injections with the aim to maximize transduction of target cell populations, while minimizing off-target effects and surgical complications. Strategic decisions on parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 53 publications
1
65
0
1
Order By: Relevance
“…In advanced choroideremia, in which the area of intact, treatable retina, choroid and RPE is limited, subretinal delivery may offer the most targeted approach currently available. In this case, the MOI is maximized, off-target exposure is minimal, and the potential for an inflammatory response is reduced because the vector is delivered directly to the target cells within an immune-privileged environment (80,81). Conversely, in early-stage choroideremia, before considerable retinal degeneration has occurred, an intravitreal approach could be considered because a larger area of the retina will be exposed to the vector.…”
Section: Understanding the Multiplicity Of Infection For Dose Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…In advanced choroideremia, in which the area of intact, treatable retina, choroid and RPE is limited, subretinal delivery may offer the most targeted approach currently available. In this case, the MOI is maximized, off-target exposure is minimal, and the potential for an inflammatory response is reduced because the vector is delivered directly to the target cells within an immune-privileged environment (80,81). Conversely, in early-stage choroideremia, before considerable retinal degeneration has occurred, an intravitreal approach could be considered because a larger area of the retina will be exposed to the vector.…”
Section: Understanding the Multiplicity Of Infection For Dose Targetingmentioning
confidence: 99%
“…However, to treat a broader area of the retina, a higher concentration of vector would be required to achieve an effective MOI over the larger treatment area. This circumstance in turn potentially raises additional safety considerations with regard to toxicity of the viral vector and inflammation; the higher total vector dose may increase the risk of shedding and biodistribution, which may be more likely to provoke a potentially harmful immune response (80,81). One option could be the use of multiple subretinal blebs instead of one single bleb; the concentration of vector would not need to be increased and there would be no increased risk of systemic exposure due to the vector being delivered directly to the target cells, as with a single bleb.…”
Section: Understanding the Multiplicity Of Infection For Dose Targetingmentioning
confidence: 99%
“…Subretinal injections in human can be performed using the "single-step" or the "two-step" approach [71]. With the "single-step" approach the fluid, containing the gene therapy vector, is directly delivered into the subretinal space without previous retinal detachment [22].…”
Section: Subretinal Injectionmentioning
confidence: 99%
“…The "two-step" approach consists of first the generation of a bleb in the subretinal space by injection of a balanced salt solution (BSS), followed by injection of the therapeutic agent using a controlled flow rate [4,5,72]. The second approach offers several advantages like the possibility to better assess the direction of bleb spread as well as to minimize vector loss by misguided injection [71]. The subretinal surgery and injection is a specialized technique and can in principle be executed by surgeons operating an ophthalmic surgery robot to obtain most reproducible results.…”
Section: Subretinal Injectionmentioning
confidence: 99%
“…In glaucoma, complement activation is dysregulated at early stages when the retina-blood barrier is intact, which would prevent administered CR2-Crry protein from reaching C3d deposits. Retinal gene therapy based on intravitreal injection of adeno-associated virus vectors, bypasses retina-blood or other cellular barriers, and locally supplies intrinsic, long-term expression of their cargo 82 . We showed that delivery of CR2-Crry via intravitreal AAV2 provided RGCs and the inner retina with a sustained Crry overexpression that regulated pathogenic C3 overactivation.…”
Section: Aav-mediated Gene Therapy For Targeted Cr2-crry Delivery To mentioning
confidence: 99%